Study of the improvement in the performance coefficient of machines operating with three reservoirs. (15th November 2004) - Grosu, L.; Feidt, M.; Benelmir, R.
The authors propose, in the first step of this paper, a unified description of machines operating with three reservoirs: refrigerating machines, heat pumps, thermotransformers, using a finite time thermodynamic approach. The incidence on the COP definitions is presented. A sensitivity study is made: performance coefficient function of variables and parameters. The calculation for each machine type is conducted for two possible cases: endoreversible machine (without internal entropy creation) and endo et exo irreversible machine (with entropy creation). The influence of the heat transfer law type is enlightened. In the second step of this paper, we propose an optimisation of performance coefficient for each type of machine with finite time constraints on the total conductance of the system.